A case for antibiotic perturbation of the microbiota leading to allergy development. (November 2013) - Reynolds, Lisa A; Finlay, B Brett
The use of antibiotics to treat pathogenic bacterial infections has been one of the greatest contributions to human health, yet antibiotic use also perturbs the communities of commensal and symbiotic bacteria that reside in the intestine of mammals. The microbiota are critical for normal immune development and for maintaining intestinal homeostasis, and disruption of the microbiota has been linked to the emergence of allergic disease both in humans and in animal models. The evidence and mechanisms for antibiotic-mediated disruptions leading to the onset of allergic disease at mucosal surfaces is discussed, as well as the future challenges for the field. A more complete understanding of the mechanisms by which the intestinal microbiota modulate allergic disease development will allow for interventions to counter the potentially adverse effects of antibiotic treatment on the microbiota.